A Comparative Study of Salivary pH and Composition between Semi-Vegetarian Dentistry Students from the Adventist University of the Philippines and Omnivore Dentistry Students from the University of the Philippines Manila/ Janine Marie B. Arboleda and Erika Mari B. Castro. - Arboleda, Janine Marie B., Author; Castro, Erika Mari B., Author .; Santos, Jessica K. R., Technical adviser and Co-Author.; Laureta, Cristina M., Faculty Co-Author .
Introduction: Salivary biochemical indicators like calcium and phosphate play their
respective roles in determining caries susceptibility of an individual (Kaur et al, 2012).
The ionic concentration of calcium and phosphate in saliva is responsible for the
maintenance of equilibrium between demineralization and remineralization of dental hard
tissues within the oral cavity. These salivary parameters can be used as a diagnostic tool
for caries risk assessment. This study looked closely at the differences of calcium and
phosphate content and pH level of saliva from semi-vegetarian and omnivore
participants
Materials and Methods: A comparative study with stratified random sampling was done
among volunteer dentistry students pre-screened with a questionnaire and 3-day dietary
record, of which 13 were semi-vegetarians and 15 were omnivores, aged 18-25 years,
from Adventist University of the Philippines (AUP) and University of the Philippines
Manila (UPM). Unstimulated saliva was collected from participants. They were asked to
lean forward over the test tube and funnel while they avoid swallowing. Saliva collection
lasted for 10 minutes. An atomic absorption spectrometer (AAS) and ultraviolet-visible
spectroscopy (UV-Vis) were employed in determining the amount of calcium and
phosphate in saliva respectively. A universal pH paper was used to assess salivary pH
levels. Data was tabulated and analyzed using t-test
Results: Mean salivary calcium concentration is 2.16 mg/L for semi-vegetarians and 1.54
mg/L for omnivores. At 5% level of significance, significant evidence shows differences
in salivary calcium composition (P value is 0.024 < 0.05) of semi-vegetarian and
omnivore students. Mean salivary phosphate concentration is 2.33mg/L for semi-vegetarians and 2.01 mg/L for omnivores. Mean salivary pH level of semi-vegetarians is
6.5 while omnivores have a mean pH of 6.4. Both groups’ salivary pH level ranging from
6-7 are within normal salivary pH level range (5.75-7.05) (Singh et al, 2013). At 5% level
of significance, there is no significant evidence for differences in salivary pH (P value is
0.482 > 0.05) and phosphate composition (P value is 0.858 > 0.05) of both groups
Conclusion: The semi-vegetarian dentistry students have a significantly higher salivary
calcium level compared to omnivore dentistry students. Differences in salivary pH and
phosphate between semi-vegetarians and omnivores are not statistically significant. Semi-vegetarians may be less susceptible to dental caries.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Saliva; Dental caries Prevention; Calcium; Phosphate